Evidence for Protein Leverage in Children and Adolescents with Obesity - Saner Christoph; Tassoni Daniella; Harcourt Brooke E; Kao Kung-Ting; Alexander Erin J; McCallum Zoe; Olds Timothy; Rowlands Alex V; Burgner David P; Simpson Stephen J; Raubenheimer David; Senior Alistair M; et al. (WILEY, 2022)
Objective
The aim of this study was to test the protein leverage hypothesis in a cohort of youth with obesity.
Methods
A retrospective study was conducted in a cohort of youth with obesity attending a tertiary weight management service. Validated food questionnaires revealed total energy intake (TEI) and percentage of energy intake from carbohydrates (ì), fats (ï), and proteins (%EP). Individuals with a Goldberg cutoff >= 1.2 of the ratio of reported TEI to basal metabolic rate from fat-free mass were included. A subgroup had accelerometer data. Statistics included modeling of percentage of energy from macronutrients and TEI, compositional data analysis to predict TEI from macronutrient ratios, and mixture models for sensitivity testing.
Results
A total of 137 of 203 participants were included (mean [SD] age 11.3 [2.7] years, 68 females, BMI z score 2.47 [0.27]). Mean TEI was 10,330 (2,728) kJ, mean ì was 50.6% (6.1%), mean ï was 31.6% (4.9%), and mean %EP was 18.4% (3.1%). The relationship between %EP and TEI followed a power function (L coefficient -0.48; P < 0.001). TEI was inversely associated with increasing %EP. In the subgroup with < 60 min/d of moderate to vigorous physical activity (n = 48), lower BMI z scores were associated with higher %EP and moderate ì.
Conclusions
In youth with obesity, protein dilution by either carbohydrates or fats increases TEI. Assessment of dietary protein may be useful to assist in reducing TEI and BMI in youth with obesity.